POTRET SISTEM PERKAWINAN MASYARAKAT TENGGER DI TENGAH MODERNITAS INDUSTRI PARIWISATA (Solidarity: Journal of Education, Society and Culture, 2012)
Tengger society are among the rare people who still maintained the values, norms, rules and customs as guidelines for living. In the middle of the globalizaion, Tengger people are able to integrate modern and traditional elements, so that people are able to follow contemporary development on the one side and preserve culture on the other side. Its culture, especially marriage, is unique and very interesting to be studied. In this study the authors used qualitative research methods. Data is obtained through field observations, interviews, and documentation. This research found many uniqueness in Tengger mariage such as debt dowry with a pledge of marriage locally known as “sri kawin kalih ringgit arto perak utang.” To understand the marriage of Terngger society, scholars need to study in the process of marriages, dowry, nicnaming after marriage, family relationships, in which all of those aspects are interrelated and influenced each other.